The role of laparoscopy in the management of infertility - انطكلي علي; سحر طاهر حسن; باسل محمد محمد (Latakia University Journal -Medical Sciences Series, 2023)
The advancement of new perspectives in assisted reproductive technology (ART) through the use of modern infertility evaluation techniques has led clinicians to reassess how infertility should best be treated. The usefulness of laparoscopy in the diagnostic work-up of infertile patients or in patients who are unresponsive to fertility treatments is debatable. The purpose of this review is to define the role of laparoscopy in the management of infertility, which is one of the most controversial aspects of reproductive medicine. To the best of our knowledge, laparoscopy is currently not a routine step in the evaluation of infertile women; every patient and clinical condition must be assessed individually. In this review, we investigated the effectiveness and the utility of laparoscopy as a diagnostic and therapeutic tool in the management of infertility.